Specific lipolytic activity in fungus collected from sugarcane bagasse - Bessa, Dâmaris Hadassa Rangel Fonseca; de Souza Castro, Carlos Frederico; Souza, Amanda Oliveira; de Menezes Filho, Antonio Carlos Pereira; Gonçalves, Mariana Costa Mello [UNESP] (Centro Universitario de Maringa, 2021)
Lipases are enzymes which catalyze chemical reactions, especially lipidic bonds. Enzymes may be retrieved from lipolytic fungi which produce high rates of lipases from a carbon source. Fungus previously selected from sugarcane bagasse underwent submersed fermentation with extra-virgin olive oil as the carbon source. Broth produced by the fungus was analyzed by spectrophotometry with substrate p-NPB and results were analyzed at 5% level. Current assay identified fungus which was capable of growth in a mineral medium with sole lipid carbon source and quantifies specific activities of lipases by substrate p-NPB. Best rates of specific lipid activities of the three fungi were 8.004 U mg-1, 5.897 U mg-1, 5.077 U mg-1, for fungus Paecilomyces formosus (first isolate), Paecilomyces formosus (second isolate) and Aspergillus tubingensis, which are rates cited for the first time for the three fungi. When compared to other microorganisms in the literature, they are higher and more active to be used in industrial processes.
Atividade específica lipolítica em fungos coletados do bagaço de cana-de-açúcar
Keywords: Aspergillus tubingensis; Lipases; Microbiology; Paecilomyces formosus